Improved limit to the diffuse flux of ultra-high energy neutrinos from the Pierre Auger Observatory - Almela, Daniel Alejandro; Asorey, Hernán Gonzalo; Bertou, Xavier Pierre Louis; Dasso, Sergio Ricardo; Dova, Maria Teresa; Etchegoyen, Alberto; Figueira, Juan Manuel; Filevich, Alberto; Freire, Martín Miguel; Garcia, Beatriz Elena; Golup, Geraldina Tamara; Gonzalez Albarracin, Flavia Alejandra; et al. (American Physical Society, 2015)
Fil: Almela, Daniel Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Instituto de Tecnologías En Detección y Astropartículas; Argentina